Energy storage system policies: Way forward and opportunities for emerging economies - Sani S.B.; Celvakumaran P.; Ramachandaramurthy V.K.; Walker S.; Alrazi B.; Ying Y.J.; Dahlan N.Y.; Rahman M.H.A. (Elsevier Ltd, 2023)
Energy policy; Energy storage; Gas emissions; Greenhouse gases; Battery storage system; Developed economies; Energy storage systems; Energy storage technologies; Level playing fields; Renewable energies; Renewable energy integrations; United States of America; Storage as a service (STaaS)